2022
DOI: 10.3389/fpsyg.2022.867606
|View full text |Cite
|
Sign up to set email alerts
|

Fear and Challenges of Nursing Students Being in Hospital for Clinical Posting During the COVID-19 Pandemic: An Exploratory Survey

Abstract: BackgroundThe world is facing unprecedented challenges in the face of a global pandemic (COVID-19). The institutions resumed nursing students’ clinical experiences as an earlier part of their curriculum, which was transitioned to a virtually delivered format due to global disaster. Therefore, working through this pandemic in hospital posting is challenging and fearful for nursing students. The aim of this study was to measure the fear of COVID-19 and the challenges faced by nursing students when posted in hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The mean level of fear of COVID-19 was 16.86 (SD = 6.14) out of a possible score of 35. This finding is in line with the rather limited previous literature [30][31][32]. Yet, scores in this study were lower than those reported from studies conducted in Mexico (25.71) [33] and Thailand (25.6) [34].…”
Section: Discussionsupporting
confidence: 90%
“…The mean level of fear of COVID-19 was 16.86 (SD = 6.14) out of a possible score of 35. This finding is in line with the rather limited previous literature [30][31][32]. Yet, scores in this study were lower than those reported from studies conducted in Mexico (25.71) [33] and Thailand (25.6) [34].…”
Section: Discussionsupporting
confidence: 90%
“…The COVID-19 pandemic has made hospital clinical placements challenging and frightening for intern nurses, who fear incubating the virus and spreading it to their loved ones and colleagues [ 31 ]. Intern nurses have been deployed to COVID-19 departments, taking on roles typically filled by registered nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Mostafa and Abu Zead (2021) found that most nursing interns initially showed reluctance to work in isolation units and care for COVID-19 patients due to fear of infection [ 38 ]. Aslan and Pekince (2021) [ 39 ] and Rana et al (2022) [ 31 ] found that 61.1% and 68.1% of students had a moderate fear of contracting the infection, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The readiness of the students in the actual hospital experience is not enough due to fact of 2-year discouragement of the government which to prevent the contagious of the coronavirus and to provide safety and secure the health of the student inside the university (Leaver et al, 2022). The fear of the students regarding the global outbreak and the worry of transmitting the virus from other people to the family is one of the factors that will limit the experience in actual setup in clinical exposure, the need to implementation of a new scheme in terms of innovative and creative strategies to prevent the existing challenges in the nursing academe is significant for the exposure of the nursing students (Rana et al, 2022). Lastly, many nursing students are worried about the health situation due to the global outbreak in 2020, which greatly affected the knowledge, skill, and attitude of the nursing students in clinical exposure as a part of the nursing education curriculum.…”
Section: Introductionmentioning
confidence: 99%